Designing sustainable barrier-free learning facilities for community colleges / Alice Sabrina Ismail and Ezlina Mohd Esa - Ismail, Alice Sabrina; Mohd Esa, Ezlina (Universiti Teknologi MARA, Perak, 2022)
Community College is a higher education system under the Department of Polytechnic Studies and Community Colleges, Ministry of Higher Education. The institution channels training and skills needed through short courses offered to various levels of society. The concept of learning and evaluation of Community Colleges is different from most local Institutions of Higher Learning (IPT) as it places more emphasis on practical learning (skill) than theory. In this regard, community colleges need to be sustainable in providing quality, high-tech and holistic education for students from various backgrounds to pursue training and studies in technical and vocational fields, including people with disabilities. However, in recent years, many criticisms surfaced on the rights of the disabled to have equal access to higher education due to decreasing barrier-free design facilities in the higher learning institutions in which the provisions of these facilities are not well distributed and insufficient in the campus area. Hence, this study aims to identify and assess the barrier-free design facilities' current provision on four community colleges campuses in Malaysia, followed by analyzing the person with disabilities perceptions on these barrier-free facilities, using a mixed methodology approach of qualitative (direct -observation) and quantitative (survey) through the pragmatism research paradigm. Findings relating to better space making, spatial arrangement, and accessibility to learning facilities are crucial to fulfilling the needs of the disabled students in the community colleges for learning purposes. Hence, recommending better design preferences for a sustainable learning environment is essential to policymakers, related authorities, and designers to improve the target group's demand. This is essential to increase the accessibility for the disabled students in their community colleges for sustainable learning built environment.